The wins of the grassroots climate movement in the University of California - Nelson, Monica; Gere, Cathy; Cooper, Adam; Thackray, Varykina G.; Aron, Adam R. (Frontiers in Education, 2025)
As the climate and ecological predicament worsens, too many people seem to be waiting for policy to be implemented from “on high.” Yet the history of many social struggles shows us that achieving policy wins requires a strong push from below. Here we recount how members of the climate justice organization The UC San Diego Green New Deal were critical to reorienting the climate policy of a very large institution, the 10 campus University of California, as well as winning important climate actions at UC San Diego itself. We discuss three campaigns: Decarbonization and Electrification, Cutting Ties with Fossil Finance, and Climate Education for All. From shifting the focus to emission reductions rather than carbon offsets, to pushing Chase Bank out of the campus student center, to providing new undergraduate curricula, these wins are now reverberating throughout higher education in the United States and beyond. This movement has also provided an important pedagogical role by teaching organizing and activist skills to undergraduates so they can go forth and fight for their futures.